2009
DOI: 10.1080/02701367.2009.10599533
|View full text |Cite
|
Sign up to set email alerts
|

Preadolescent Female Development Through Sport and Physical Activity

Abstract: Youth development research has found that children become more engaged and benefit more from being incorporated as decision makers. Thus participation helps promote development and encourages engagement. Based in theories of engagement and free-choice learning, the current research focused on a program combining sport/physical activity, life skills, and mentoring while promoting healthy life choices for preadolescent girls of color The co-investigators, all women, conducted two 2-hr visits per week for two 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…More than one data collection technique (e.g., interviews, document analysis, and observation) was used in 32 studies. Furthermore, 27 studies included data collected from multiple samples, such as athletes and coaches/program leaders/teachers (e.g., Armour et al, 2013 ; Koh et al, 2014 ) or athletes and parents (e.g., Bruening et al, 2009 ; Fuller et al, 2013 ). The use of multiple data collection techniques can provide opportunities for data triangulation (Patton, 2014 ) and was a strength of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one data collection technique (e.g., interviews, document analysis, and observation) was used in 32 studies. Furthermore, 27 studies included data collected from multiple samples, such as athletes and coaches/program leaders/teachers (e.g., Armour et al, 2013 ; Koh et al, 2014 ) or athletes and parents (e.g., Bruening et al, 2009 ; Fuller et al, 2013 ). The use of multiple data collection techniques can provide opportunities for data triangulation (Patton, 2014 ) and was a strength of the studies reviewed.…”
Section: Resultsmentioning
confidence: 99%
“… Armour et al ( 2013 ), Bean et al ( 2014 ), Brown and Fry ( 2011 ), Camiré and Trudel ( 2010 ), Camiré et al ( 2009a ), Camiré et al ( 2012 ), Camiré et al ( 2013 ), Cowan et al ( 2012 ), Daud and Carruthers ( 2008 ), Dinanthompson et al ( 2008 ), Escarti et al ( 2010 ), Flett et al ( 2013 ), Fraser-Thomas and Côté ( 2009 ), Goudas and Giannoudis ( 2010 ), Gould et al ( 2007 ), Hardcastle et al ( 2015 ), Harrist and Witt ( 2012 ), Harwood ( 2008 ), Neely and Holt ( 2014 ), Holt et al ( 2008 ), Holt et al ( 2012 ), Holt et al ( 2013 ), Iachini et al ( 2014 ), Light ( 2010 ), Olushola et al ( 2013 ), Strachan et al ( 2011 ), Trottier and Robitaille ( 2014 ), Turnnidge et al ( 2012 ), Walsh ( 2007 ), Walsh et al ( 2010 ), Weiss et al ( 2013 ), Wright and Burton ( 2008 ) Transfer activities Ways in which transfer of personal and social skills learned in sport to other life situations may occur. Allen et al ( 2015 ), Bruening et al ( 2009 ), Koh et al ( 2014 ), Camiré et al ( 2009a ), Camiré et al ( 2012 ), Chinkov and Holt ( 2015 ), Flett et al ( 2013 ), Goudas and Giannoudis ( 2010 ), Gould et al ( 2007 ), Holt et al ( 2013 ),...…”
Section: Methodsmentioning
confidence: 99%
“…Along the same lines, it has been found that when women engage in recreational PSA, their self-esteem and self-efficacy improve, leading to greater psychological wellbeing (Hornibrook et al, 1997;Taylor, 2014) and improving their perception of their health (Taylor et al, 2013) and of their level of physical skill (Culp, 1998;Marsh & Peart, 1988), as well as their social relations (Bruening, Dover, & Clark, 2009). Furthermore, socialisation and the network of positive relations becomes a fundamental factor in this kind of programme, since the level of commitment to the activity and the construction of meaningful relationships with peers are directly related (Allender, Cowburn, & Foster, 2006;Flintoff & Scraton, 2001;Roura Coma, 1999;Whittington, 2006).…”
Section: Recreational Programmes Exclusively For Womenmentioning
confidence: 97%
“…Por las tardes hay menos gente y se juega más, pero yo he elegido el de las mañanas por las relaciones" (Ainara). Bruening et al (2009), el hecho de que el programa esté dirigido exclusivamente a las mujeres ayuda a crear ese sentimiento grupal y de comunidad, ya que se construyen relaciones significativas con iguales (Allender et al, 2006).…”
Section: Perception Of the Female Basque Pelota Players: "A Programmeunclassified
See 1 more Smart Citation